Transformational Leadership, Job Satisfaction, and Organizational Culture in the Dynamics of Performance Improvement of ASN in Jombang - Maryati, Tatik; Realita , Tasnim Nikmatullah (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study examines how transformational leadership style and organizational culture impact employee performance, with job satisfaction as a mediating factor among sub-district employees in Jombang Regency. The decline in performance across seven sub-districts is the basis for this research. It employs a quantitative approach, using a sample of 86 civil servants from a population of 125 employees selected through purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (SmartPLS 4). The results indicate that transformational leadership style and organizational culture positively affect job satisfaction and employee performance. Job satisfaction serves as a partial mediating variable. This study highlights the need to improve transformational leadership skills and establish an inclusive organizational culture to boost the performance of civil servants at the sub-district level